(untitled) (Research, Society and Development, 2021)
Any stimulus, whether intrinsic or extrinsic, triggers a biological response that refers to stress. Stress is a characteristic element of the natural world, operating in almost all biological systems, and in every situation that distances living systems from a constant physiological condition. Physiological responses can be used as stress indicators, and may be generalized responses to a stimulus, mediated by the sympathetic nervous system and the hypothalamic-pituitary-adrenal axis through the action of hormones such as adrenaline and corticosteroids. Some stimuli activate one system more than another, a condition that can occur due to the specific roles of the stimulus on the systems, being superimposed on their generalized roles. The amplitude of the hormonal response can correlate with the intensity of the stimulus, and any change indicates that the body is responding. Thus, this article aims to verify the physiological behavior of the body in the face of stress. For that, a bibliographic review was carried out in which publications that addressed the subject were used in the MEDLINE® (PubMed®) and Scientific Electronic Library Online (SciELO) databases between the years 1983 and 2020. Conclusion: The human body is affected in different ways by the stressful event, the impacts of stressors exert a stimulating effect, giving rise to behavioral and physiological reactions used to face these events, since the adaptive response is fundamental to survival. There are great individual differences in dealing with stress, however, the mechanisms underlying how we respond support physiological functions, maintaining homeostasis and contributing to adaptation.